Polyploidy in vertebrate ancestry: Ohno and beyond - Furlong, R; Holland, P (2004)
Over 30 years ago, Susumu Ohno proposed that two rounds of polyploidy occurred early in vertebrate evolution. We re-examine this proposal using three recent lines of evidence. First, total gene number estimates from completely sequenced genomes suggest an increase in total gene number somewhere along the vertebrate or prevertebrate lineage, compatible with Ohno's model. Second, analyses of homeobox and other genes from amphioxus reveal very extensive gene duplication specifically on the vertebrate lineage. This refines the timing of putative polyploidy to after the divergence of amphioxus and vertebrates. Third, the existence of four-fold paralogy regions in the human genome is suggestive of two rounds of polyploidy, although other explanations are possible. We propose an experimental test, based on chromosomal localization of genes in amphioxus, that should resolve whether paralogy regions are indeed remnants of duplication in vertebrate ancestry. © 2004 The Linnean Society of London, Biological Journal of the Linnean Society.